Hepatic PEComa: a potential pitfall in the evaluation of hepatic neoplasms - Khan, Hadi Mohammad (BMJ Publishing Group, 2014)
Perivascular epithelioid cell tumour (PEComa) of the liver is very uncommon and may be overlooked in the clinical and histological differential diagnosis of a liver tumour. We report the case of an incidentally discovered liver mass suspicious for hepatocellular carcinoma, which on biopsy was suggestive of a pseudocyst but after resection was found to be hepatic PEComa with some of the usual characteristics of this neoplasm as well as several less familiar features. We have also reviewed cases of hepatic PEComa from the literature in order to provide insight into recognising possible PEComa preoperatively and assessing its risk of malignancy after diagnosis.